A step-length formula for conjugate gradient methods / Adam Ajimoti Ishaq, Tolulope Latunde and Kazeem Babatunde Akande - Ishaq, Adam Ajimoti; Latunde, Tolulope; Akande, Kazeem Babatunde (Universiti Teknologi MARA, 2020)
A newly step-length formula is proposed for implementing conjugate gradient methods’ algorithm to solve unconstrained optimization problems. The unified formula for obtaining step-length does not involve any matrix operation. Numerical results obtained are graphically illustrated using performance profiling software. This showed that the new formula performs efficiently in terms of computational efforts and execution time compared with some existing formulae for obtaining the step-length without line search procedures.